1976
DOI: 10.1002/ajpa.1330440304
|View full text |Cite
|
Sign up to set email alerts
|

A twin study of dental dimension. II. Independent genetic determinants

Abstract: To demonstrate the presence of independent genetic determinants of multiple correlated tooth dimensions from twin data, a multivariate analysis was performed on the covariance matrices of monozygotic and dizygotic within-pair differences for mesiodistal and buccolingual dimensions of 28 teeth of the secondary dentition. The results provided strong evidences that the correlation among tooth dimensions is primarily genetic in origin, probably attributable to the pleiotropic action of either independent genes or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
37
0

Year Published

1981
1981
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(42 citation statements)
references
References 5 publications
5
37
0
Order By: Relevance
“…Our findings, however) contradict both these predictions and further add to the evidence that females and males do not differ significantly in their response to asymmetrogenic factors (Perzigian, 1977;Townsend and Garcia-Godoy, 1984). Significant arcadal differences in the magnitude of fluctuating odontometric asymmetry (Tables 2, 4, and 5 ) confirm earlier findings that maxillary teeth are less well buffered than mandibular teeth (Garn et al, 1966;Harris and Nweeia, 1980;Siegel and Doyle, 19751, and in turn support the contention that tooth dimensions along the two arcades are largely independently determined (Garn et al, 1968;Kieser et al, 1985b;Potter et al, 1976).…”
Section: Resultssupporting
confidence: 72%
“…Our findings, however) contradict both these predictions and further add to the evidence that females and males do not differ significantly in their response to asymmetrogenic factors (Perzigian, 1977;Townsend and Garcia-Godoy, 1984). Significant arcadal differences in the magnitude of fluctuating odontometric asymmetry (Tables 2, 4, and 5 ) confirm earlier findings that maxillary teeth are less well buffered than mandibular teeth (Garn et al, 1966;Harris and Nweeia, 1980;Siegel and Doyle, 19751, and in turn support the contention that tooth dimensions along the two arcades are largely independently determined (Garn et al, 1968;Kieser et al, 1985b;Potter et al, 1976).…”
Section: Resultssupporting
confidence: 72%
“…In population terms, it takes the form of a relative decrease in the correlation coefficients between opposite crown diameters both within and among the incisors and canines of both arches, such that a n orthogonal factor analysis tends to exhibit a single factor each for molar size and premolar size, but two separate factors for the mesiodistal and buccolingual dimensions of the anterior teeth. This phenomenon has now been observed to varying extent in contemporary Caucasians (Garn et al, 1968;Potter et al, 1976), PimaIndians (Potter et al, 1968), Melanesians (Kolakowski and Bailit, in preparation), Australian aboriginals (Townsend and Brown, 1979), and a Mexican cranial series (Lombardi, 1975).Interpretation of this finding has tended to be in terms of independent genetic determinants, and in deference to this view we included in the present analysis a test for the presence of any major-gene effects. However, the developmental biology of tooth formation, with its control mechanisms, tissue interactions, environmental feedback, and sequential, time-dependent phenomena (see Biggerstaff, 1979), has seemed to us t o militate against any purely genetic interpretation and to render the above phenomenon quite enigmatic.…”
mentioning
confidence: 83%
“…Many investigators reported relatively high heritability rates for dental dimensions based on family and twin studies (Garn et al, 1968;Goose 1971;Alvesalo and Tigerstedt, 1974;Potter et al, 1976;Townsend and Brown, 1978;summarized by Hillson, 1996). Mizoguchi (1977) reported the heritabilities of mesiodistal crown diameters in permanent dentitions of modern Japanese as ranging from 0.07-1.00 with an average of 0.81 in males, and from 0.41-1.00 with an average of 0.74 in females.…”
Section: Methodsmentioning
confidence: 99%